Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

If 18√8 - 8 √18 = √n, what is n?

Sagot :

Answer:

n=288

Step-by-step explanation:

Rewrite the equation as  

n

=

18

8

8

18

.

n

=

18

8

8

18

To remove the radical on the left side of the equation, square both sides of the equation.

√n

2

=

(

18

8

8

18

)

2

Simplify each side of the equation.  

Use  

n

a

x

=

a

x

n

to rewrite  

n  as  n

1

2

.

(

n

1

2

)

2

=

(

18

8

8

18

)

2

Simplify  

(

n

1

2

)

2

.  

Multiply the exponents in  

(

n

1

2

)

2

.  

Apply the power rule and multiply exponents,  

(

a

m)n

=

a

m

n

.

n

1

2

2

=

(

18

8

8

18

)

2

Cancel the common factor of  2  

Cancel the common factor.

n

1

2

2

=

(

18

8

8

18

)

2

Rewrite the expression.

n

1

=

(

18

8

8

18

)

2

Simplify.

n

=

(

18

8

8

18

)

2

Simplify  

(

18

8

8

18

)

2

Simplify each term.

Rewrite  

8  as  2

2

2

.  

Factor  

4  out of  8  

n

=

(

18

4

(

2

)

8

18

)

2

Rewrite  

4  as  2

2  

n

=

(

18√

2

2

2

8

18

)

2

Pull terms out from under the radical.

n

=

(

18

(

2

2

)

8

18

)

2

Multiply  

2  by  18  

n

=

(

36

2

8

18

)

2

Rewrite  

18

as  

3

2

2

.

Factor  

9

out of  

18

.

n

=

(

36

2

8

9

(

2

)

)

2

Rewrite  

9

as  

3

2

.

n

=

(

36

2

8

3

2

2

)

2

Pull terms out from under the radical.

n

=

(

36

2

8

(

3

2

)

)

2

Multiply  

3

by  

8

.

n

=

(

36

2

24

2

)

2

Simplify terms.

Subtract  

24

2

from  

36

2

.

n

=

(

12

2

)

2

Simplify the expression.

Apply the product rule to  

12

2

.

n

=

12

2

2

2

Raise  

12

to the power of  

2

.

n

=

144

2

2

Rewrite  

2

2

as  

2

.

Use  

n

a

x

=

a

x

n

to rewrite  

2

as  

2

1

2

.

n

=

144

(

2

1

2

)

2

Apply the power rule and multiply exponents,  

(

a

m

)

n

=

a

m

n

.

n

=

144

2

1

2

2

Combine  

1

2

and  

2

.

n

=

144

2

2

2

Cancel the common factor of  

2

.

Cancel the common factor.

n

=

144

2

2

2

Rewrite the expression.

n

=

144

2

1

Evaluate the exponent.

n

=

144

2

Multiply  

144

by  

2

.

n

=

288

Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.